O déficit de natureza nas crianças pequenas: a influência dos ambientes de aprendizagem - Santos, Sammya Danielle Florencio dos (2022)
The children in the great cities are growing up and developing themselves far way of nature and natural elements, according to Louv (2016) conceptualizes like nature déficits. Based on this assumption, our general aim of this research: understanding the learning environments utilization to bring young children closer the nature and decrease the nature déficits at pre - school. This research presents a more qualitative and descriptive approach, it is based on phenomenology of perception of Merleau-Ponty (2018). We also have as an epistemological basis of studying of philosopher Spinoza (2009) that explains the relationship and nature expression and connexion. The theorical foundation was built by Barros (2018), Freire (2013), Louv (2016), Profice (2016), Capra (2006), Tiriba (2018) and Santos (2018), Marques and Marandino (2019), Jacobucci (2008) and Rocha and Fachín-Terán (2010). The colecting data instruments’ were the studying about children and nature, and the target documents of children education, like the Diretrizes Curriculares Nacionais (2010), Base Nacional Comum Curricular(2018), Referencial Curricular Amazonense (2019) and Curriculo Escolar Municipal de Manaus (2021). The research exposes the relationship between the children and natural elements at Education Spaces, and how the term “ nature” is presented in documents of children education. The result of studying indicated that the child learns in the relationship with the world and the teacher has the important role of mediating this learning. Also it demonstrated that it is necessary to pay attention how the nature has been presented and lived by the children in pre-school, from the documents for this stage of education. In addition, a proposal for didactic sequences was generated, to be experienced by children, in formal and non-formal learning spaces, in Manaus city, to keep them closer of natural world. Key-words: Nature. Young children. Education Spaces. Pre-School.